Evaluation of FFR and CPET in patients with de novo coronary chronic total occlusion treated with DCB vs. DES - Lingli Guo; Hengdao Liu; Xi Zhao; Ting Liu; Chenyang Gao; Jihao Duan; Dongfeng Wang; Junwei Zhao; Yuzhen Wei; Ruipeng Song; Hailong Tao (Frontiers in Cardiovascular Medicine)
BackgroundDrug-coated balloon (DCB) is a novel therapeutic strategy for de novo coronary chronic total occlusion (CTO). However, fractional flow reserve (FFR), a key indicator of evaluating coronary function, and cardiopulmonary exercise testing (CPET), an important indicator of cardiopulmonary function, are rarely reported for evaluating the effectiveness of DCB in CTO lesions.Methods and resultsIn this retrospective study, 100 patients were enrolled and classified into the DCB group (n = 48) and the drug-eluting stent (DES) group (n = 52). All patients underwent coronary angiography immediately after PCI and during follow-up. Some patients underwent FFR measurement (n = 64) or CPET (n = 56) at follow-up. There was no significant difference in baseline clinical characteristics between the two groups. Compared with the DES group, the DCB group had a significantly smaller late lumen loss (LLL) (P < 0.05). Also, there was no significant difference in the proportion of FFR values ≥0.90 between the two groups at follow-up. Similarly, there was also no statistically significant difference in the CPET parameters between the two groups (P > 0.05). In addition, the incidence of MACE (major adverse cardiovascular events) showed no statistical difference during hospitalization and follow-up between the two groups (P > 0.05).ConclusionsDCB treatment for de novo CTO lesions yields FFR and CPET results comparable to DES, with an even smaller LLL. This result provides a new approach for the treatment of de novo CTO lesions.